The Use of Metrics in Daily Practice and the Perception of Psoriasis-Associated Comorbidities: Discrepancies Between Research and Real-World - Hillary T; Lambert J (Psoriasis: Targets and Therapy, 2021)
Tom Hillary,1 Jo Lambert2 1Department of Dermatology, University Hospitals Leuven, Leuven, 3000, Belgium; 2Department of Dermatology, Ghent University Hospital, Gent, 9000, BelgiumCorrespondence: Tom HillaryDepartment of Dermatology, University Hospitals Leuven, Herestraat 49, Leuven, 3000, BelgiumEmail tom.hillary@uzleuven.beObjective: To assess the feasibility of the future implementation of a recently published Belgian treat-to-target scoring in daily practice, we investigated to what extent Belgian dermatologists use metrics and take comorbidities into account in the follow-up of psoriasis patients.Methods: Belgian dermatologists were addressed to fill out an online questionnaire in April 2020.Results: A total of 149 dermatologists completed the survey. About 55% (n = 78) indicated to do a full-body examination during every visit. Psoriasis Area Severity Index (PASI) was the most frequently used clinical score: 25% (n = 35) and 61% (n = 87) indicated to use it every visit or sometimes (> 1/year), respectively. The most frequently used patient-reported outcome scoring system was the Dermatology Life Quality Index: 35% use it sometimes. Overall, there is awareness for the association with metabolic syndrome.Conclusion: Among tools for follow-up on moderate-to-severe psoriasis patients, Belgian dermatologists most frequently apply full-body examination and PASI score. Patient-reported outcome scoring systems are used infrequently. Psoriasis is perceived as a disease with comorbidities beyond the skin, especially obesity and hypertension. These real-world data on the use of clinical scores and PROs indicate a discrepancy from the academic setting in which new drugs are developed and evaluated. Furthermore, these data are imperative to estimate the feasibility of implementing a treat-to-target strategy published earlier by a Belgian expert group.Keywords: psoriasis, comorbidities, patient care, treat to target, metrics